COVID‐DAI: A novel framework for COVID‐19 detection and infection growth estimation using computed tomography images. Issue 6 (23rd February 2022) - Nazir, Tahira; Nawaz, Marriam; Javed, Ali; Malik, Khalid Mahmood; Saudagar, Abdul Khader Jilani; Khan, Muhammad Badruddin; Abul Hasanat, Mozaherul Hoque; AlTameem, Abdullah; AlKathami, Mohammad
Abstract: The COVID‐19 pandemic is spreading at a fast pace around the world and has a high mortality rate. Since there is no proper treatment of COVID‐19 and its multiple variants, for example, Alpha, Beta, Gamma, and Delta, being more infectious in nature are affecting millions of people, further complicates the detection process, so, victims are at the risk of death. However, timely and accurate diagnosis of this deadly virus can not only save the patients from life loss but can also prevent them from the complex treatment procedures. Accurate segmentation and classification of COVID‐19 is a tedious job due to the extensive variations in its shape and similarity with other diseases like Pneumonia. Furthermore, the existing techniques have hardly focused on the infection growth estimation over time which can assist the doctors to better analyze the condition of COVID‐19‐affected patients. In this work, we tried to overcome the shortcomings of existing studies by proposing a model capable of segmenting, classifying the COVID‐19 from computed tomography images, and predicting its behavior over a certain period. The framework comprises four main steps: (i) data preparation, (ii) segmentation, (iii) infection growth estimation, and (iv) classification. After performing the pre‐processing step, we introduced the DenseNet‐77 based UNET approach. Initially, the DenseNet‐77 is used at the Encoder module of the UNET model to calculate the deep keypoints which are later segmented to show the coronavirus region. Then, the infection growth estimation of COVID‐19 per patient is estimated using the blob analysis. Finally, we employed the DenseNet‐77 framework as an end‐to‐end network to classify the input images into three classes namely healthy, COVID‐19‐affected, and pneumonia images. We evaluated the proposed model over the COVID‐19‐20 and COVIDx CT‐2A datasets for segmentation and classification tasks, respectively. Furthermore, unlike existing techniques, we performed a cross‐dataset evaluation to show the generalization ability of our method. The quantitative and qualitative evaluation confirms that our method is robust to both COVID‐19 segmentation and classification and can accurately predict the infection growth in a certain time frame. Research highlights: We present an improved UNET framework with a DenseNet‐77‐based encoder for deep keypoints extraction to enhance the identification and segmentation performance of the coronavirus while reducing the computational complexity as well. We propose a computationally robust approach for COVID‐19 infection segmentation due to fewer model parameters. Robust segmentation of COVID‐19 due to accurate feature computation power of DenseNet‐77. A module is introduced to predict the infection growth of COVID‐19 for a patient to analyze its severity over time. We present such a framework that can effectively classify the samples into several classes, that is, COVID‐19, Pneumonia, and healthy samples. Rigorous experimentation was performed including the cross‐dataset evaluation to prove the efficacy of the presented technique Abstract : Graphical abstract